Mistrust A Global Perspective - Mühlfried, Florian (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book examines the social practice of mistrust through the lens of social anthropology. In focusing on the citizens of the Caucasus, a region located at the crossroads of Europe and Asia, Mühlfried counters the postcolonial discourse that routinely treats these individuals, known for their mistrust of the state, as "others." Combining ethnographic observations presenting mistrust as an observable reality with socio-political issues from a non-Western region, Mühlfried opens up a non-Eurocentric perspective on an underexplored social practice and a major counterpoint to the well-examined social phenomenon of "trust." This perspective allows for a more profound understanding of pressing issues such as populist movements and post-truth politics.